2010
DOI: 10.1186/1471-2334-10-81
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of bacterial vaginosis in relation to sexual behaviour

Abstract: BackgroundBacterial vaginosis (BV) has been most consistently linked to sexual behaviour, and the epidemiological profile of BV mirrors that of established sexually transmitted infections (STIs). It remains a matter of debate however whether BV pathogenesis does actually involve sexual transmission of pathogenic micro-organisms from men to women. We therefore made a critical appraisal of the literature on BV in relation to sexual behaviour.DiscussionG. vaginalis carriage and BV occurs rarely with children, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 102 publications
(130 reference statements)
6
105
0
7
Order By: Relevance
“…We observed that 94% of BV positive cases were married, this confirms the observation of the strong relation between sexual activity and BV acquisition reported by previous studies such as Verstraelen et al, [27], who reported that BV may be considered a sexually enhanced disease, with frequency of intercourse being a critical factor and Gallo et al, [28], who found a biological evidence of an association between semen exposure and incident BV. It was observed that 94% (31/33) of the BV positive cases were using vaginal douches which confirms that vaginal douches represent a risk factor of BV acquisition.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that 94% of BV positive cases were married, this confirms the observation of the strong relation between sexual activity and BV acquisition reported by previous studies such as Verstraelen et al, [27], who reported that BV may be considered a sexually enhanced disease, with frequency of intercourse being a critical factor and Gallo et al, [28], who found a biological evidence of an association between semen exposure and incident BV. It was observed that 94% (31/33) of the BV positive cases were using vaginal douches which confirms that vaginal douches represent a risk factor of BV acquisition.…”
Section: Discussionsupporting
confidence: 80%
“…This observation may be a possible explanation for the high prevalence of BV among African women (Allsworth and Peipert, 2007;Bukusi et al, 2006) since it is known that most L. iners strains are very weak H 2 O 2 producers. In contrast, L. crispatus is known to produce large amounts of H 2 O 2 and as such provides better colonization resistance (Antonio et al, 1999;Vallor et al, 2001;Verstraelen et al, 2009;Verstraelen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Tackling the HIV burden through eradicating BV and restoring normal vaginal microflora is currently considered part of the most promising answers to the HIV pandemic (Martin et al, 1999;Shin and Kaul, 2008;Bolton et al, 2008). The last two decades have seen a significant increase in the volume of research focusing on BV and composition of vaginal microflora (Verhelst et al, 2005;Kalra et al, 2007;Srinivasan et al, 2010;Verstraelen et al, 2010). The prevalence of BV varies widely in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…The role of sexual activity in the development of BV has been questioned for some time with increasing epidemiological and microbiological data suggesting BV may be sexually transmitted. Numerous studies have shown BV to be associated with sexual risk behaviours that typify STIs including: inconsistent or lack of condom use, new or multiple sexual partners, symptomatic female sexual partners, high frequency of sexual intercourse, young age at first sex and penile-vaginal sex [1,2,[15][16][17][18][19]. A recent qualitative study undertaken with 35 Australian women with recurrent BV supported these findings, with the majority reporting BV onset had been triggered by sexual contact [20].…”
Section: Introductionmentioning
confidence: 92%